The Association between Matrix Metalloproteinase-9 (MMP-9) Immunohistochemical Expression and Gleason Grading System International Society of Urological Pathology (ISUP) in Prostate Adenocarcinoma - Sefparina Harahap; Jessy Chrestella; Lidya Imelda Laksmi; T. Ibnu Alferraly; Betty Betty (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2026)
Background Prostate cancer is the fourth ranked malignancy and the eighth leading mortality worldwide. The Gleason grading system is used to evaluate the tumor grade. The highest the score, the worst and the most aggressive the nature of the tumor, which associated with invasive behaviour. In prostate carcinoma, Matrix Metalloproteinase-9 (MMP-9) is involved in all stages of cancer cell progression include proliferation, angiogenesis, apoptosis, epithelial-mesenchymal transition (EMT) and metastasis. MMP-9 degrade the surrounding tumor matrix and neural tissue during perineural invasion in prostate carcinoma which is a prerequisite for invasion and metastasis. The aim of this research is to evaluate the correlation of MMP-9 immunohistochemical expression with the Gleason Grading System International Society of Urological Pathology (ISUP) of prostate adenocarcinoma. Methods Cross sectional analytic study of 32 samples were diagnosed with prostate adenocarcinoma at H. Adam Malik General Hospital Medan. Staining was performed using a polyclonal antibody rabbit MMP-9 immunohistochemistry (Bioenzy) which would appear positive in the cytoplasm and in stroma of the tumor cell at a dilution of 1: 100 (overnight). MMP-9 expression was assessed semi quantitatively based on intensity and tumor cell distribution with four-tier expression categories. Data analysis was tested with the Kruskal-Wallis test. Results Most cases (56,25%) were strongly positive with MMP-9 and MMP-9 immunohistochemical expression has a significant relationship with Gleason Grading ISUP System of prostate adenocarcinoma (p:0.001). Conclusion There was a significant association between MMP-9 immunohistochemical expression and the Gleason Grading ISUP System of prostate adenocarcinoma. Keyword: Prostate adenocarcinoma, ISUP, Gleason grading, matrix metalloproteinase-9